Investigating the optimistic in-vitro and in-vivo therapeutic effects of wild grape: Vitis jacqumantii R. Parker - Tour Jan; Syed Wadood Ali Shah; Nasrullah Khan; Mohammad Sohail Ahmad; Ibrahim A. Saleh; Mohammad K. Okla; Mostafa A. Abdel-Maksoud; Abdullah A. AL-ghamdi; Yasmeen A. Alwasel; Hamada AbdElgawad (Heliyon)
Vitis jacquemontii R. Parker is a wild grape traditionally used by indigenous people as a substitute for cultivated grapes. However, its therapeutic effects have not been extensively studied. In this study, we investigated the antioxidant, anticholinesterase, analgesic, and antidepressant properties of V. jacquemontii. The antioxidant potential of this wild fruit plant was evaluated using two widely recognized assays: 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-asino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). In-vitro anticholinesterase effects were determined by assessing butyrylcholinesterase (BChE) and acetylcholinesterase (AChE) inhibition. The analgesic activity was assessed through writhing and tail immersion test models, while the antidepressant effect was evaluated using forced swimming and tail suspension test models. Results revealed the exceptional potential of V. jacquemontii as a valuable natural resource. The fruit extract (VJF-Crd) demonstrated remarkable free radical scavenging abilities, with an impressive IC50 value of 34.96 μg/mL for DPPH and 56.48 μg/mL for ABTS. The leaf extract (VJL-Crd) also exhibited considerable antioxidant properties, with IC50 values of 73.68 μg/mL for DPPH and 86.72 μg/mL for ABTS. Furthermore, VJF-Crd and VJL-Crd extracts displayed potent inhibitory activity against cholinesterase enzymes, with VJF-Crd demonstrating strong inhibition and VJL-Crd showing moderate inhibition. In terms of analgesia, these extracts exhibited dose-dependent responses in various pain models, with significant protection against acetic acid-induced writhing and tail immersion, showcasing their potential as natural pain relievers. Moreover, both VJF-Crd and VJL-Crd extracts displayed a notable decrease in immobility in the forced swimming and tail suspension test models, indicating their potential as natural antidepressants. These findings underscore the untapped potential of V. jacquemontii as a source of valuable chemical constituents. The isolation and identification of phyto-constituents from this plant hold promise for new bioactive compounds, particularly in pain management. This study sheds light on the multifaceted medicinal attributes of V. jacquemontii and opens new avenues for developing natural remedies for different ailments, especially pain management.